The results of the effectiveness of pharmaceutical treatment of chronic gastritis with erosions associated with Helicobacter pyloriwith azithromycin and amoxicillin in the elderly - T. E. Afanasenkova; E. E. Dubskaya (Антибиотики и Химиотерапия)
Digestive diseases, chronic gastritis with erosions being one of them, are common in elderly patients. Helicobacter pylori infection is one of the etiopathogenetic factors of chronic gastritis. Eradication therapy is currently considered one of the main treatments and prophylaxis of H. pylori infection. However, the increase in the duration of eradication therapy leads to an increase in the frequency of side effects, especially in the gastrointestinal tract, as well as the risk of cardiotoxicity which results in a decrease in the patient's compliance with therapy.The aim of the study was to evaluate the effectiveness of H. pylori eradication in the treatment of chronic gastritis with erosions using azithromycin and amoxicillin.Material and methods. A clinical and endoscopic examination of 134 patients with chronic gastritis with erosions associated with H. pylori was carried out. Depending on the treatment regimen, all patients were divided into 2 groups. The first group consisted of patients who received azithromycin for 5 days and amoxicillin for 10 days, omeprazole 2 times a day for 14 days, then once daily for 4 weeks, De-Nol for 28 days. In the second group, patients received clarithromycin and amoxicillin for 14 days, omeprazole 2 times a day for 14 days, then once daily for 4 weeks, De-Nol for 28 days. Control studies were conducted 6 weeks after the end of drug administration.Results. Abdominal and sternal pain, dysphagia, nausea, heartburn, vomiting, bloating, stool disorders — diarrhea or constipation — were the predominant complaints in the elderly patients. Assessment of the local effectiveness of the applied eradication regimens allows the select of the most effective and safe therapyregimens.Conclusion. Given the short course of administration of azithromycin (5 days) and  (10 days), these drugs can be used in patients with low adherence to treatment, as well as for prevention of complications caused by antibiotics in elderly patients who are constantly taking medications for other diseases.